Analysis of Colored Variable Message Signs for Visibility and Comprehensibility. Issue 1 (January 2020) - Kersavage, Kristin; Guler, S. Ilgin; Pietrucha, Martin
Variable message signs (VMS) present traffic information to motorists in either real-time or asynchronous static conditions, for example, such as safety information. This information can consist of early warning, advisory, and alternative route messages, and travel time information. Many U.S. states currently use VMS. New technology allows for messages to be configured using colored fonts and backgrounds, but whether these new features affect the visibility and comprehensibility of VMS is not known. Expert interviews and laboratory tests were conducted to examine the effectiveness of the use of different wording, text, and background colors, and types of information on a VMS. The expert interviews provided information on best practices related to VMS design and use, and provided feedback on the preliminary test panel candidates, which were modified and used in the final group of test stimuli. The first laboratory experiments compared signs based on the reaction times and viewing distances of participants reading and interpreting sign information. The shortest reaction times occurred when: (a) messages displayed time only, (b) route numbers were displayed as text, not as part of route shields, and (c) color was not used, but if color were used it would be on a black background and to show congested travel times. The second laboratory experiments compared signs based on the correctness of the participants' responses about travel times or distances. The results determined there were no differences in identifying the travel times or distances; however, using MI instead of MILES can increase the percentage of correct responses relative to the identification of distances to road junctions or hazards.